2019
DOI: 10.3892/ijmm.2019.4428
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA CYTOR promotes tamoxifen resistance in�breast cancer cells via sponging miR‑125a‑5p

Abstract: development of resistance to endocrine therapy, such as tamoxifen, remains a tricky clinical problem during the treatment of breast cancer. Accumulating evidence suggested that dysregulation of long noncoding (lnc_RNAs contributes to the development of tamoxifen resistance. In the current study, via screening, cytoskeleton regulator RNA (cYTOR) was identified as the most significantly elevated lncRNA in the established tamoxifen resistant McF7 cell lines (McF7/TAM1 and McF7/TAM2) compared with the parental McF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 35 publications
1
53
2
Order By: Relevance
“…Mechanistically, YAP and Runx2 together displayed an oncogenic activity by hindering lncRNA MT1DP in a FoxA1‐dependent manner in liver cancer 47 . Other lncRNAs that are regulated by Hippo signalling pathway include cytoskeleton regulator RNA (CYTOR), 50,51 non‐coding RNA activated by DNA damage (NORAD) 52 and H19 53 . LncRNA CYTOR, also known as long intergenic ncRNA 00 152 (LINC00152), is located on chromosome 2p11.2 with a length of 828 nucleotides 54 .…”
Section: Regulatory Network Of Lncrnas and Hippo Signalling Pathway Imentioning
confidence: 99%
“…Mechanistically, YAP and Runx2 together displayed an oncogenic activity by hindering lncRNA MT1DP in a FoxA1‐dependent manner in liver cancer 47 . Other lncRNAs that are regulated by Hippo signalling pathway include cytoskeleton regulator RNA (CYTOR), 50,51 non‐coding RNA activated by DNA damage (NORAD) 52 and H19 53 . LncRNA CYTOR, also known as long intergenic ncRNA 00 152 (LINC00152), is located on chromosome 2p11.2 with a length of 828 nucleotides 54 .…”
Section: Regulatory Network Of Lncrnas and Hippo Signalling Pathway Imentioning
confidence: 99%
“…CYTOR has been characterized as an oncogenic lncRNA in many types of cancers [15,16]. In cancers, CYTOR is overexpressed to promote cancer development by increasing cell proliferation and suppressing cell apoptosis [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…However, in vivo animal model experiments and clinical trials are needed to test our hypothesis. It is also worth noting that CYTOR suppress cell apoptosis in both cancers [15,16] and OA. Therefore, CYTOR may play similar roles in cell apoptosis in different human diseases.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA CYTOR promotes TAM resistance by increasing serum response factor (SRF) and activating the MAPK signaling pathway by sponging miR-125a-5p in MCF-7/TAM cells. 81 Sun et al identified a novel AIs / / / / / Notes: "↑" represents upregulation; "↓" represents downregulation; "/" represents not mentioned.…”
Section: Tamoxifenmentioning
confidence: 99%
“…68 TINCR sponges miR-125b and promotes TZB resistance in HER-2+ BC cells. 100 Other lncRNAs such as FTH1P3, 67 LINC00511, 69 ATB, 103 CYTOR, 81 DSCAM-AS1, 83,84 ROR, 86 ADAMTS9-AS2, 91 LINC00894-002, 92 NONHSAT101069, 29 and PRLB 77 sponge specific miRNAs to regulate drug resistance in BC.…”
Section: Cernasmentioning
confidence: 99%